2016
DOI: 10.1161/circinterventions.116.004336
|View full text |Cite
|
Sign up to set email alerts
|

Sealing Intermediate Nonobstructive Coronary Saphenous Vein Graft Lesions With Drug-Eluting Stents as a New Approach to Reducing Cardiac Events

Abstract: S aphenous vein graft (SVG) atherosclerosis after coronary artery bypass grafting (CABG) remains the primary cause of late graft failure, with SVG obstruction rates as high as 50% having been reported 10 years post-CABG. . Patients were randomized (1:1) to DES implantation (SVG-DES) or medical treatment (SVG-MT) of the target SVG lesion. The primary efficacy outcome was the first occurrence of MACE defined as the composite of cardiac death, myocardial infarction, or coronary revascularization related to the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The ITA, an endothelialized conduit, demonstrates excellent longterm patency due to its resistance to atherosclerosis. The use of radial artery grafts, once considered challenging, has become more prevalent due to refinements in surgical technique and patient selection criteria [31][32][33]. Advancements in graft selection in CABG have revolutionized the field of cardiac surgery, enhancing patient outcomes and redefining surgical strategies.…”
Section: Advancements In Graft Selectionmentioning
confidence: 99%
“…The ITA, an endothelialized conduit, demonstrates excellent longterm patency due to its resistance to atherosclerosis. The use of radial artery grafts, once considered challenging, has become more prevalent due to refinements in surgical technique and patient selection criteria [31][32][33]. Advancements in graft selection in CABG have revolutionized the field of cardiac surgery, enhancing patient outcomes and redefining surgical strategies.…”
Section: Advancements In Graft Selectionmentioning
confidence: 99%
“…The results were attributed to late (>2 year) restenosis after SVG stenting that resulted in loss of the early beneficial effect of stenting. 70 Patients with intermediate SVG lesions are currently treated medically with control of diabetes, smoking cessation, and aggressive lipid lowering. Although mean low-density lipoprotein level was <70 mg/dL in VELETI II, SVG failure rates were high, suggesting that even more strict lipid control may be necessary.…”
Section: Treatment Of Intermediate Svg Lesionsmentioning
confidence: 99%
“…The results were attributed to late (>2 year) restenosis after SVG stenting that resulted in loss of the early beneficial effect of stenting. 70…”
Section: Treatment Of Intermediate Svg Lesionsmentioning
confidence: 99%
“…Degenerated SVG lesions tend to be more lipid-rich with poorly developed or even absent fibrous cap compared to native coronary vessel lesions. Interestingly, it has been suggested that sealing even mild or moderate SVG lesions with DES does not necessarily reduce the incidence of long-term MACE compared to medical treatment alone [ 46 , 47 ]. The deployment of stents in SVGs may well lead to a more enhanced inflammatory and thrombotic reaction, which may be difficult to reverse in the acute phase.…”
Section: Stent Choice In Svg Lesionsmentioning
confidence: 99%